Mortality after hospital discharge for people with schizophrenia or bipolar disorder: retrospective study of linked English hospital episode statistics, 1999-2006. - Hoang, U; Stewart, R; Goldacre, M (2011)
OBJECTIVE: To investigate whether the mortality gap has reduced in recent years between people with schizophrenia or bipolar disorder and the general population. DESIGN: Record linkage study. SETTING: English hospital episode statistics and death registration data for patients discharged 1999-2006. PARTICIPANTS: People discharged from inpatient care with a diagnosis of schizophrenia or bipolar disorder, followed for a year after discharge. MAIN OUTCOME MEASURES: Age standardised mortality ratios at each time, comparing the mortality in people with schizophrenia or bipolar disorder with mortality in the general population. Poisson test of trend was used to investigate trend in ratios over time. RESULTS: By 2006 standardised mortality ratios in the psychiatric cohorts were about double the population average. The mortality gap widened over time. For people discharged with schizophrenia, the ratio was 1.6 (95% confidence interval 1.5 to 1.8) in 1999 and 2.2 (2.0 to 2.4) in 2006 (P < 0.001 for trend). For bipolar disorder, the ratios were 1.3 (1.1 to 1.6) in 1999 and 1.9 (1.6 to 2.2) in 2006 (P = 0.06 for trend). Ratios were higher for unnatural than for natural causes. About three quarters of all deaths, however, were certified as natural, and increases in ratios for natural causes, especially circulatory disease and respiratory diseases, were the main components of the increase in all cause mortality. CONCLUSIONS: The total burden of premature deaths from natural causes in people with schizophrenia or bipolar disorder is substantial. There is a need for better understanding of the reasons for the persistent and increasing gap in mortality between discharged psychiatric patients and the general population, and for continued action to target risk factors for both natural and unnatural causes of death in people with serious mental illness.